Dynamic mechanical properties of nanoparticle-stabilized foam concrete (NFC) - Zhixing Li; Wensu Chen; Guoxing Sun; Yanru Chen; Zhejian Li; Huawei Li; Hong Hao (Case Studies in Construction Materials)
Nanoparticle-stabilized foam concrete (NFC) is a lightweight and eco-friendly construction material that was recently developed by the authors. NFC can reduce cement usage by 15–40 % while maintaining similar strength as conventional foam concrete (FC). NFC holds significant potential for various applications, such as sacrificial layer for structural protection considering its sound energy absorption capacity and building envelopes designed to withstand dynamic loads such as impact and blast loading. Therefore, it is essential to understand the dynamic mechanical behaviour of NFC. In this study, the Split Hopkinson Pressure Bar (SHPB) system was employed to investigate and quantify mechanical properties of NFC with two dry densities of 980 and 1330 kg/m³ under dynamic compression with strain rates up to 240 s−1. Specifically, the failure progress, failure patterns, stress-strain curves, dynamic compressive strength and energy absorption were analysed and compared. Testing results indicate that dynamic mechanical properties of NFC are strain-rate dependent, and NFC with lower density exhibits greater sensitivity to strain rate. Dynamic increase factor (DIF) of compressive strength and energy absorption capacity of NFC were derived, and the corresponding empirical equations were proposed. This study provides insights into the dynamic mechanical properties of NFC, facilitating its further development and application as a lightweight construction material.